R1234yf and R1234ze(E) as low-GWP refrigerants for residential heat pump water heaters. (October 2017) - Nawaz, Kashif; Shen, Bo; Elatar, Ahmed; Baxter, Van; Abdelaziz, Omar
Highlights: A calibrated model has been used to evaluate the performance of hydrofluoroolefins (HFOs) as alternative refrigerants for HPWH. UEF, FHR and heat pump COP have been evaluated for R1234yf, R1234ze(E) and R134a. Various design parameters have been considered to evaluate the impact on the performance. Critical performance parameters for the heat pump and water tank have been evaluated and compared to the baseline system. Abstract: Owing to the growing concerns about the relatively high global warming potential (GWP) of current refrigerants, a serious effort is in progress to find lower-GWP substitutes. The hydrofluoroolefin (HFO)-based refrigerants R1234yf and R1234ze(E) are being considered for use in multiple heating, ventilation, air conditioning, and refrigeration applications because of their very low GWP. A study was conducted to model a residential heat pump water heater using these HFOs. A system model was calibrated using experimental data and the calibrated model was used to evaluate the potential of HFOs to replace R134a. A series of parametric analyses were used to investigate the impacts of condenser wrap pattern, condenser tube size, evaporator size, and heat loss factor from the storage tank. It has been shown that both R1234yf and R1234ze(E) can be substituted for R134a with comparable performance and no substantial modifications to the original system. This study presents a detailed feasibility analysis for successful replacement of high-GWP refrigerants with low-GWP refrigerants with acceptable performance.